User Pairing for Multiuser SC-FDMA Transmission over Virtual MIMO ISI Channels - Ruder, Michael; Dang, Thi Uyen Ly; Gerstacker, Wolfgang (GLOBECOM 2009 - 2009 IEEE Global Telecommunications Conference, 2010)
This paper proposes different criteria for user pairing for a virtual multiple-input multiple-output (V-MIMO) single-carrier frequency-division multiple access (SC-FDMA) transmission over intersymbol interference (ISI) channels. Two users, equipped with a single antenna each, transmit their data in the same time slot and frequency band. The receiver at the base station (BS) is assumed to have two antennas and separates both users with a multiuser equalizer. For this, linear minimum mean-squared error (MMSE) equalization and successive interference cancellation (SIC), respectively, are chosen. Various pairing criteria are proposed and compared by simulations for a transmission in the uplink of E-UTRA Long Term Evolution (LTE). The simulation results indicate that well-designed user pairing strategies yield significant gains compared to random user pairing. It is shown that the proposed novel bit error rate (BER) pairing achieves a significant performance gain compared to capacity pairing for a SIC receiver and higher order modulatio